Population Priorities for Successful Aging: A Randomized Vignette Experiment. (6th June 2018) - Whitley, Elise; Benzeval, Michaela; Popham, Frank
Abstract: Objectives: Aging populations have led to increasing interest in "successful aging" but there is no consensus as to what this entails. We aimed to understand the relative importance to the general population of six commonly-used successful aging dimensions (disease, disability, physical functioning, cognitive functioning, interpersonal engagement, and productive engagement). Method: Two thousand and ten British men and women were shown vignettes describing an older person with randomly determined favorable/unfavorable outcomes for each dimension and asked to score (0–10) how successfully the person was aging. Results: Vignettes with favorable successful aging dimensions were given higher mean scores than those with unfavorable dimensions. The dimensions given greatest importance were cognitive function (difference [95% confidence interval CI] in mean scores: 1.20 [1.11, 1.30]) and disability (1.18 [1.08, 1.27]), while disease (0.73 [0.64, 0.82]) and productive engagement (0.58 [0.49, 0.66]) were given the least importance. Older respondents gave increasingly greater relative importance to physical function, cognitive function, and productive engagement. Discussion: Successful aging definitions that focus on disease do not reflect the views of the population in general and older people in particular. Practitioners and policy makers should be aware of older people's priorities for aging and understand how these differ from their own.